Tradisi Mustami'an: Kerapan Sapi dalam Pembelajaran Bahasa Arab dari Perspektif Antropologi di Pondok Pesantren Madura - Jailani, Mohammad (Balai Diklat Keagamaan Bandung, 2024)
From an anthropological standpoint, this research examines the acculturation of the culture of livestock frequency and mustami'an in studying Arabic at Madura Islamic boarding schools. The research takes a qualitative method focused on case studies, with data gathered through observation, interviews, and documentation. The research focuses on Islamic boarding schools and their many components. Data analysis employs the Miles and Huberman technique, which includes data reduction, presentation, and verification. The study's findings highlight the need of combining Arabic linguistics with local culture in distant locations, which helps to preserve cultural legacy like cow frequency and mustami'an through learning that incorporates local terminology and cultural values into teaching materials.